FORMULATION OF COLD DRINKS ON THE BASIS OF DECOCTION OF DRUG PLANTS - Turebekova Gaukhar Zahievna; Shapalov Shermakhan Kuttibayevich; Alpamysovа Gulnzhayna Baigonysova; Issayev Gany Isaulu; Bitimirovа Aliya; Altybaev Zhaksylyk Mamyrbekovich; Yergubekova Zhanat Saparbekovna; Lyubchyk Svitlana (Scientific Journal of Pedagogy and Economics, 2019)
It is proposed to use natural supplements using drug plants of South Kazakhstan region (Turkestan region) in this paper. Such composition of cold drinks allows not only to allay thirst, but also to compensate necessary vitamins and other useful substances in a human body. There are more than 20,000 plant species in Kazakhstan, 6,000 of which contain biologically active substances. But there are other compounds in the composition of plants that are not desirable in the composition of drinks. Therefore, it is very important to separate and obtain necessary biologically active compounds, which positively influence the useful and organoleptic properties of drinks. We have studied trends and prospects of the market of various soft drinks in Kazakhstan and abroad. The developed recipes for enriched cold drinks using dietary supplements derived from Turkestan region drug plants have high biological activity. The obtained cold drinks will be the first domestic products, obtained with the use of Turkestan region drug plants.